Pengaruh Penggunaan Google Class Room Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SMP Negeri 7 Bukittinggi - Alhamda, Robi; C, Charles (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
If you want to take the next step later, you can use the Google Class Room teacher to use PAI on the seventh day of SMPN 7 Bukittinggi. If you are active and want to connect your teacher with your knowledge, you can use teacher feedback to communicate through Google Class Room student learning outcomes in PAI subjects at SMP N Bukittingg You can compare the approach of correctional institutions with the correctional system by using the correctional institution approach to make comparisons that later became popular with methods that you can use to create a holistic-contextual view of lazy data collection. The population of group VII of SMP N 7 was taken from group VII.1 227 years ago. The technology may be an example of adding data to data that you can no longer access and use. Imagine experiencing norms and homogeneity. The instrument in this study used was a documentary film. The number of numbers obtained was 35,248 then 2,0395. This number can be increased to a higher level in Google Class Room if you simply use the simple PAI path for Google Class Room a class VII student at SMP N 7 Bukittinggi.